A tumor microenvironment model coupled with a mass spectrometry system to probe the metabolism of drug-loaded nanoparticles. Issue 69 (31st July 2019) - Lin, Ling; Zheng, Yajing; Wu, Zengnan; Zhang, Wei; Lin, Jin-Ming
Abstract : A tumor microenvironment vasculature model coupled with a mass spectrometry system to probe the metabolism of drug-loaded nanoparticles. Abstract : This study describes a novel integrated microfluidic platform with microvessel network channels which are connected to an electrospray ionization-mass spectrometer (ESI-MS), allowing real-time probing of nanoparticle (NP) drug delivery in vascular niche around tumors and understanding the drug delivery efficacy in a realistic tumor microenvironment.